2013
DOI: 10.3145/epi.2013.ene.11
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas de información geográfica para unidades de información

Abstract: Estefanía Aguilar-Moreno es licenciada en documentación y máster en sociedad de la información y el conocimiento por la Universitat Oberta de Catalunya (UOC). Trabaja en temas relacionados con la inteligencia competitiva y colabora como consultora en los Estudios de Ciencias de la Información y de la Comunicación de la UOC. Actualmente cursa los estudios de doctorado en el programa de la ResumenSe muestran los sistemas de información geográfica (Geographic Information Systems, GIS) como tecnología de soporte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The previous systematic literature review on GIS use in LIS identified two main categories of use of GIS in LIS research (Bishop and Mandel, 2010): analyzing service area populations (data from outside libraries) and facilities management (data from inside libraries). Aguilar-Moreno and Grannell-Canut (2013) reviewed the literature on uses of GIS in libraries. They categorized the work into three groups: visualizing information to help libraries in making decisions, search interfaces and incorporating GIS data as a library resource.…”
Section: Resultsmentioning
confidence: 99%
“…The previous systematic literature review on GIS use in LIS identified two main categories of use of GIS in LIS research (Bishop and Mandel, 2010): analyzing service area populations (data from outside libraries) and facilities management (data from inside libraries). Aguilar-Moreno and Grannell-Canut (2013) reviewed the literature on uses of GIS in libraries. They categorized the work into three groups: visualizing information to help libraries in making decisions, search interfaces and incorporating GIS data as a library resource.…”
Section: Resultsmentioning
confidence: 99%